Effectiveness of Digital Marketing: Tourism Websites Comparative Analytics Based on AIDA Model - Meera Prathapan; Sajin Sahadevan and Zakkariya K.A (International Journal of Innovative Research & Studies, 2018)
Tourism has become a priority sector in the world with its contribution towards the economic development of the nations. Globally, Kerala is known for its exotic places and their efforts to promote Kerala as a tourist destination. The state as well as the private organisations are taking vigorous promotional efforts to attract large number of visitors throughout the year. At this context, present study was done to compare the Kerala tourism website of the government with its competitors to evaluate the promotional efforts taken by them. The study has adopted AIDA model in digital marketing for measuring the promotional efforts of these websites. For comparison, the web analytics was done using the analytical softwares Alexa and SEMrush. The findings of the study revealed the importance of considering different key performance indicators in AIDA such as number of visitors, unique visitors, bounce rate, average duration of visit, most visited pages and click- through rate to improve the quality of the websites.